(Un)wanted Female Offspring: From a Traditional Cultural Preference for Sons to a Pragmatic Preference for Daughters in the Republic of Korea and Its Emanation in Chosen Demographic Issues (Politeja, 2025)
The neo-Confucian tradition in South Korea had influenced the number of female Koreans that were born due to the patrilineality-caused aversion to daughters and pre- and post-natal sex selection. The introduction of ultrasonographic devices even deepened the sex ratio at birth (SRB), resulting in the state forbidding their use for prenatal sex determination. Since the 2000s, a preference for daughters has been visible, and SRB is considered natural. The paper aims to show changes in South Korean culture and approach towards the sex of the offspring. It also aims to prove that a stronger cultural aversion to daughters in the past in South Korea has changed as an result of cultural and societal transformations, but also surprisingly of the traditional approach to gender roles – it is not generally emphasized and it can accelerate the drop in an already low total fertility rate (TFR) in this country.